Learning environments of chemistry classes in selected secondary schools - Rivera, Thelma A.
This study was undertaken to determine what psychosocial variations in chemistry classroom environments exist in selected secondary schools, how different psychosocial learning environments in chemistry classes relate to student's attitude toward and achievement in chemistry, and how attitude toward chemistry relates to achievement in this subject. The study also attempted to find out if teachers and students perceive the same chemistry classroom environments similarly. This study is limited to third year chemistry classes in selected schools in Quezon CVity. Seven hundred twenty third year high school chemistry students and 36 teachers from 72 classes in 12 big schools in Quezon City were involved in the study. Three researcher-made instruments were used in the study. These were the Learning Environment Scale (LES) to assess the classroom environment. Attitude toward Chemistry Scale (ATCS) to assess the student's attitude toward chemistry, and the Chemistry Achievement Test (CAT) which aimed to assess the students' achievement in chemistry. The factor analyses of the students' responses to the 76 items of the Learning Environment Scale (LES) and responses to the 20 items of the Attitude toward Chemistry Scale (ATCS) yielded 7 LES factors and 2 attitude factors respectively. The seven LES factors are: Students' Interest (Factor I), Teacher Support (Factor II), Fairness and Clarity of Rule and Tasks in the Classroom (Factor III), Teacher Encouragement (Factor IV), Student Participation (Factor V), Classroom Ventilation (Factor VI), and Classroom Space (Factor VII) while two attitude factors are: Liking for and Competence in Chemistry (A Factor I) and, Perceptions and Beliefs about Chemistry (A Factor II).
The results of the study show that there are psychosocial variations in the chemistry class environment as perceived by the students from school to school. Using Pearson correlation technique, all the seven LES factors are directly related to the attitude factors, i.e, the more favorable the classroom environemnt is, the more positive are the attitudes toward chemistry, and vice versa. The seven LES factors are also directly related to chemistry achievement, i.e., the more favorable the classroom environment is, the higher is the chemistry achievement, and vice versa. Perceptions and Beliefs about Chemistry significantly influence chemistry achievement. A student who has more positive perceptions and beliefs about chemistry will exhibit a good performance in chemistry, and vice versa. Using multiple regression analyses, Students' Interest, Teacher Support, Fairness and Clarity of Rule and Tasks in the Classroom, Student Participation, and Perceptions and Beliefs about Chemistry were found to be good predictors of chemistry achievement. Among the five predictors, Fairness and Clarity of Rule and Tasks in the Classroom has the most positive influence on chemistry achievement. It has both direct and indirect effects (through Perceptions and Beliefs about Chemistry) on chemistry achievement. Teachers and their students significantly differ in the way they perceive the same classroom environment. The teachers perceive the same classroom environment more highly than their students do. From the results of the study, a typical chemistry classroom environment as perceived by 720 third year high school students in Quezon City is described as follows: The students do not have high attentive interest in chemistry and do not enjoy the class that much. Only a few participate in class recitations and discussions as most would prefer to be passive listeners. On the other hand, the teacher uses different modes of teaching to get the attention and interest of the students, and to enliven the class. The teacher is not only supportive, he/she also encourages the students to participate in class recitations and discussions, disciplines the class to be calm and orderly, treats them fairly, and explains the lessons well. The classroom is fairly ventilated and there is enough space for classwork.
Available to the general public.
Thesis (Doctor of Philosophy in Science Education)--University of the Philippines, April 1998.
Keywords: Classroom environments; Learning; Chemistry; High schools